Cost effectiveness analysis of a randomised trial of acupuncture for chronic headache in primary care. Issue 7442 (15th March 2004) - Wonderling, David; Vickers, Andrew J; Grieve, Richard; McCarney, Rob
Abstract: Objective To evaluate the cost effectiveness of acupuncture in the management of chronic headache. Design Cost effectiveness analysis of a randomised controlled trial. Setting General practices in England and Wales. Participants 401 patients with chronic headache, predominantly migraine. Interventions Patients were randomly allocated to receive up to 12 acupuncture treatments over three months from appropriately trained physiotherapists, or to usual care alone. Main outcome measure Incremental cost per quality adjusted life year (QALY) gained. Results Total costs during the one year period of the study were on average higher for the acupuncture group (£403; 768;€598) than for controls (£217) because of the acupuncture practitioners' costs. The mean health gain from acupuncture during the one year of the trial was 0.021 quality adjusted life years (QALYs), leading to a base case estimate of £9180 per QALY gained. This result was robust to sensitivity analysis. Cost per QALY dropped substantially when the analysis incorporated likely QALY differences for the years after the trial. Conclusions Acupuncture for chronic headache improves health related quality of life at a small additional cost; it is relatively cost effective compared with a number of other interventions provided by the NHS.